2017
DOI: 10.1038/s41598-017-14650-z
|View full text |Cite
|
Sign up to set email alerts
|

Cross platform analysis of transcriptomic data identifies ageing has distinct and opposite effects on tendon in males and females

Abstract: The development of tendinopathy is influenced by a variety of factors including age, gender, sex hormones and diabetes status. Cross platform comparative analysis of transcriptomic data elucidated the connections between these entities in the context of ageing. Tissue-engineered tendons differentiated from bone marrow derived mesenchymal stem cells from young (20–24 years) and old (54–70 years) donors were assayed using ribonucleic acid sequencing (RNA-seq). Extension of the experiment to microarray and RNA-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 80 publications
2
23
0
Order By: Relevance
“…A follow up study of the microarray data by Popov et al has shown that several members of the ephrin receptor family, important for cell-cell signaling, are significantly downregulated in aged/degenerative cells but interestingly, reconstituted some cellular features such as self-renewability and wound healing potential are greatly improved. Cross platform analysis of transcriptomic data investigated connections between age, gender and sex hormones during the development of tendinopathy and identified that in old males decreased expression of CRABP2 leads to cell proliferation, whereas in old females it leads to cellular senescence [32]. This study gives the important notion that tendon degenerative diseases may need to be treated differently in males and females because alternative mechanisms may be involved [32].…”
Section: Tissue Changes: Histopathological Structural Cellular Epimentioning
confidence: 95%
See 1 more Smart Citation
“…A follow up study of the microarray data by Popov et al has shown that several members of the ephrin receptor family, important for cell-cell signaling, are significantly downregulated in aged/degenerative cells but interestingly, reconstituted some cellular features such as self-renewability and wound healing potential are greatly improved. Cross platform analysis of transcriptomic data investigated connections between age, gender and sex hormones during the development of tendinopathy and identified that in old males decreased expression of CRABP2 leads to cell proliferation, whereas in old females it leads to cellular senescence [32]. This study gives the important notion that tendon degenerative diseases may need to be treated differently in males and females because alternative mechanisms may be involved [32].…”
Section: Tissue Changes: Histopathological Structural Cellular Epimentioning
confidence: 95%
“…Cross platform analysis of transcriptomic data investigated connections between age, gender and sex hormones during the development of tendinopathy and identified that in old males decreased expression of CRABP2 leads to cell proliferation, whereas in old females it leads to cellular senescence [32]. This study gives the important notion that tendon degenerative diseases may need to be treated differently in males and females because alternative mechanisms may be involved [32]. Moreover, a number of studies based on RNA sequencing were recently released, revealing higher cellular heterogeneity in tendon tissues than ever expected.…”
Section: Tissue Changes: Histopathological Structural Cellular Epimentioning
confidence: 99%
“…Given the wide inter- and intra-species variation in tendon structure and function, as well as between sex variance in tendon homeostasis, 17 further work is required to investigate the influencers of normal ageing in tendon. This is particularly true in relation to the non-coding RNAs as this is a rapidly expanding area and one which is still poorly understood.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“… 15 A transcriptomic meta-analysis study of both tendon and tissue-engineered tendon constructs demonstrated distinct differences in how ageing affects males and females. 17 As the incidence and anatomical location of tendinopathy is known to be influenced by sex, 18 this difference in normal sex-related ageing may be pivotal in understanding the predisposition to, and therefore ability to prevent disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation